The impact of cytochrome 450 and Paraoxonase polymorphisms on clopidogrel resistance and major adverse cardiac events in coronary heart disease patients after percutaneous coronary intervention - Zhang, Zhaowei (BMC Pharmacol Toxicol, 2020)
BACKGROUND: Clopidogrel is an inactive prodrug, it catalyzed into its active form by Cytochrome 450 and Paraoxonase-1(PON-1). polymorphisms of genes encoding these enzymes will affect the efficacy of Clopidogrel. The main objective of our study was to investigate the association of CYP2C19*2, CYP2C19*3 and PON-1Q192R polymorphisms with Clopidogrel resistance and major adverse cardiac events in Jin Hua district in the middle of Zhe Jiang Province in China. METHODS: One hundred sixty coronary heart disease patients with percutaneous coronary intervention, who were followed-up for 1 year, were enrolled in our study. These patients were co-administered aspirin 100 mg/d and clopidogrel 75 mg/d following a loading dose of 300 mg. The ADP-induced platelet aggregation rate was measured by Platelet aggregator. Genotypes of CYP2C19*2, CYP2C19*3, PON-1Q192R were determined using Sanger sequencing in all patients. Various clinical data were collected. RESULTS: The frequencies of CYP2C19*2, CYP2C19*3 and PON-1Q192R homozygous mutant genotypes were significantly lower in non-responders than those in responders. After for all variables, CYP2C19*2, CYP2C19*3 and PON-1Q192R independently increased the risk of clopidogrel resistance with adjusted ORs 46.65(95% CI,1.77–25.04; p = 0.005); 22.74(95% CI, 3.11–166.27; p = 0.002); 5.69 (95% CI,1.06–30.47; p = 0.042). Over a follow-up of 12 months, the incidence of major adverse cardiac events (MACE) in CYP2C19*1/*2, *1/*3, *2/*2, *2/*3 was significantly higher than no mutant genotype (18/40vs.2/63,3/9vs.2/63, 11/6vs.2/63, 7/1vs2/63, respectively). There was no significant correlation between PON-1Q192R mutant allele and MACE. CONCLUSION: Our study was first time to report on CYP2C19 and PON-1 polymorphisms in Jin Hua population in the middle of Zhe Jiang province in China. The carriage of CYP2C19*2 or *3 mutant allele significantly reduced the platelet response to clopidogrel and increase the MACE. The carriage of PON-1 mutant allele also significantly reduced the platelet response to clopidogrel, but would not increase the major adverse cardiac events after 1 year follow-up. TRIAL REGISTRATION: ChiCTR, ChiCTR1800018316. Registered 11 September 2018 – prospective registered, http://www.chictr.org.cn/edit.aspx?pid=30927&htm=4.